Research progress on the generation of environmental persistent free radicals on the surface of fine particulates during the combustion of organic solid waste - YANG Guohao; ZHANG Bennong; HU Yanjun* (能源环境保护)
Environmental persistent free radicals (EPFRs) are new environmental pollutants with long half-life, stability and persistence, and have serious environmental toxicity effects. EPFRs can be formed in the process of organic solid waste combustion through the thermochemical decomposition of organic precursors on the surface of environmental media. At present, the research on EPFRs in combustion process is still at the initial stage. In order to clarify the generation mechanism of EPFRs in combustion system, this review systematically summarizes relevant studies on surface EPFRs of combustion source particulates, briefly describes the types of EPFRs and their detection and analysis methods. The distribution characteristics of surface EPFRs from combustion source particulate matter, the formation mechanism of EPFRs formed by transition metal redox, and the influence of external factors such as oxygen content and light on the formation of EPFRs are summarized. The formation and evolution of EPFRs under different temperature gradients are discussed, and the future research directions are prospected. It is proposed that the competitive reaction and synergistic behaviors between organic precursors and transition metal oxides on the particle surface of combustion source under multifactorial coupling are important to reveal the mechanism of EPFRs generation, as well as the core content of understanding the evolutionary control of EPFRs from the microscopic molecular scale, which is expected to provide direction and basis for controlling EPFRs formation in organic solid waste combustion process.